SCIENTIFIC BASES OF OPTIMIZATION OF ORGANIZATION TECHNOLOGICAL DECISIONS OF CIVIL CONSTRUCTION IN THE COASTAL ZONE: Array - Honcharenko, D.; Menejljuk, I.; Nikiforov, O. (Municipal economy of cities (Technical science), 2019)
The volume of civil construction in Ukraine is constantly increasing, however, the conditions of civil construction are more complicated than other types of construction. No studies have been found in the normative and reference literature studying optimization of organizational technological solutions of civil construction in the coastal zone throughout the life cycle. The high social, economic and technical effect of solving the problem of choosing rational organizational and technological solutions of civil construction in the coastal zone makes the research topic highly relevant. Purpose: development of scientific provisions for optimization of organizational technological solutions of civil engineering in the coastal zone throughout the life cycle. Analysis of information sources showed that housing conditions are extremely volatile, so it is important to investigate the impact of changes in organizational and technological decisions on the main indicators, especially on the budget and duration of construction. It was found number of unique factors that allowed distinguishing a new subject of research: the organizational and technological system "civil construction in the coastal zone". Optimization tasks at different stages of the life cycle and under different conditions were highlighted for this subject. Optimization algorithm was developed. Classifications of indicators and factors were proposed that can be used to optimize the system under consideration. The algorithm of choice of indicators and factors was developed. Some technical details of the optimization process using experimental-statistical modeling were described. Development of scientific and methodological bases for optimization of organizational and technological solutions of civil construction in the coastal zone allows increasing the economic, technical, as well as social and environmental efficiency of this production.